Dual-faced guardians: SGLT2 inhibitors’ kidney protection and health challenges: a position statement by Kasralainy nephrology group (KANG) - Amin Roshdy Soliman; Mohamed Elkhatib; Sahier El-Khashab; Rasha Ahmed Darwish; Ahmed Fayed; Tarek S. Abdelaziz; Hany Hammad; Rabab Mahmoud Ahmed; Hoda Abdelhamid Maamoun (Diabetology & Metabolic Syndrome)
Abstract Background SGLT2 inhibitors represent a revolutionary drug class that delivers benefits exceeding those of diabetes management alone. Initially approved for type 2 diabetes management, research continually demonstrates their protective effects on kidney function across several nephrological conditions, including acute kidney injury (AKI), chronic kidney disease (CKD), dialysis-dependent kidney failure, anemia, metabolic bone disease, polycystic kidney disease (PKD), glomerulonephritis, and kidney transplantation. Purpose This study aims to identify how SGLT2 inhibitors modify nephrological care by investigating their mechanisms of action, therapeutic outcomes, and potential applications in multiple kidney diseases. It summarizes clinical trial data alongside mechanistic insights to provide a comprehensive assessment of therapeutic outcomes beyond diabetes mellitus. Findings Numerous clinical studies have demonstrated that SGLT2 inhibitors reduce kidney disease progression in patients with or without diabetes. These findings indicate that SGLT2 inhibitors provide kidney protection by enhancing tubuloglomerular feedback, improving renal blood flow, and reducing inflammation and ischemic tissue damage. They also provide cardiovascular benefits to dialysis patients while maintaining effective blood flow during dialysis. SGLT2 inhibitors should not be used in autosomal dominant polycystic kidney disease (ADPKD) outside clinical trials. The potential impact of SGLT2 inhibitors on bone mineral health, particularly regarding bone mineral density (BMD) reduction and fracture risk, requires careful consideration, especially in patients with pre-existing bone health concerns. Kidney transplant recipients benefit from SGLT2 inhibitors’ protective effects on kidney health and assistance with diabetes management; however, further research is needed on drug compatibility with immunosuppressants and infection prevention.